PELAYANAN KESEHATAN SAPI BALI DI WILAYAH LINGKAR KAMPUS UNIVERSITAS UDAYANA BUKIT JIMBARAN KECAMATAN KUTA SELATAN KABUPATEN BADUNG - I. N. Suarsana; I. K. Suatha; P. Sampurna; I. M. Kardena; I. W. Suardana; I. H. U Utama (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
One of the obstacles that are often faced in livestock raising is a matter of disease. Even sometimes farmerssuffered economic losses and no longer breeding due to the death of livestock. The health service is one ofthe factors that determine the success of a farm. The aim of this implemented service to improve health ofbali cattle by through health services which include spraying, provision of vitamins and treatment of cattle atUniversity of Udayana Campus around area Jimbaran Hill. Results of community service activities on cattleat University of Udayana Campus around area Jimbaran Hill, showed a positive response and a highenthusiasm of livestock farmers, that shown with the large number of cattle (37 cattle ) which can be given alivestock health services. The number and type of service animal on the farm is dominated by provision ofvitamins as much as 32 cattle (86.48%), spraying action of 30 cattle (81.08%), worm medication of 7 cattle(18.92%), and administration of antibiotics of 6 cattle (16.21%). Breeders appreciate the service activities ofthe Institute for Research and Community Services and hope a sustainable because it was felt useful.